Collection of highly aligned electrostrictive graft elastomer nanofibers using electrospinning in a vacuum environment - Rao, Vivek S. (Kansas State University, 2009)
Electrospinning is one of the most versatile methods used to fabricate nanofibers. Sub micron and nano level fibers can be continuously produced with the help of an external electric field induced on the polymer melt. These nanofibers can be used in a large variety of applications such as biosensors, three dimensional tissue scaffolds, composites, electronic devices, etc. A unique feature of electrospinning is its ability to work with different fiber assemblies. This helps in making application specific changes and also increases the quality and performance of the fibers. PEO (polyethylene oxide) and electrostrictive graft elastomer (an electroactive polymer developed by NASA) were used in our experiments which focus on controlling the shape and alignment of the fibers. Electroactive polymers (EAP’s) are seen as the basis for future artificial muscles because of their ability to deform when external voltage is applied and quickly recover to their original form when the polarity of the applied voltage is reversed. Hence, aligned fibers of the electrostrictive graft elastomer were produced to mimic the alignment in human muscle fibers. Alignment of fibers is the main objective of this research and was facilitated using vacuum technology. The research was basically divided into three phases, starting with checking of the repeatability of the previously developed techniques using polyethylene oxide. Next, the electrostrictive graft elastomer was spun using the electrospinning techniques and was checked for alignment using the Coaxial Electrode method and PLC controlled secondary electric field method. Finally, a vacuum chamber was designed and built with new components and the elastomer was tested for improved alignment in vacuum using the PLC controlled secondary electric field method.
Keywords: Elestrospinning; Alignment of nanofibers; Chemistry, Polymer (0495); Engineering, Mechanical (0548); Physics, General (0605)